2011
DOI: 10.1155/2011/540396
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Prediction Equations of Spirometric Lung Function for Caucasian Adults 20 to 90 Years of Age: Results from the Canadian Obstructive Lung Disease (COLD) Study and the Lung Health Canadian Environment (LHCE) Study

Abstract: These spirometry reference equations, derived from randomly selected population-based cohorts with stringently monitored lung function measurements, provide data currently lacking in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…To determine the relationship between the SR and EFL, eighty-four young healthy subjects were analyzed from published data (Dominelli et al, 2013, 2011, 2015b, 2014b). All subjects were non-smokers and had normal spirometry (Tan et al, 2011). Resting spirometric data was assessed by a qualified respirologist who was blinded to whether or not subjects developed EFL during exercise.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relationship between the SR and EFL, eighty-four young healthy subjects were analyzed from published data (Dominelli et al, 2013, 2011, 2015b, 2014b). All subjects were non-smokers and had normal spirometry (Tan et al, 2011). Resting spirometric data was assessed by a qualified respirologist who was blinded to whether or not subjects developed EFL during exercise.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures adhered to the Declaration of Helsinki and were approved by the Clinical Research Ethics Board at the University of British Columbia. Subjects had a wide range of exercise participation (recreational to national calibre athletics), did not report any current or previous cardiorespiratory ailments and had spirometry parameters within normal limits (Tan et al 2011; Table 1). Although not universally established, studies in which conjugates of oestrogen and progesterone have been measured have demonstrated significant inter-and intrasubject variability with respect to hormone levels throughout the menstrual cycle, but with no effect on submaximal exercise ventilation (Beidleman et al 1999;MacNutt et al 2012).…”
Section: Subjectsmentioning
confidence: 99%
“…When compared with height‐matched men, women have smaller lungs (Tan et al . ) and conducting airways (Mead, ; Sheel et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from the Canadian Cohort of Obstructive Lung Disease (COLD) to assign a binary COPD status to individuals upon their creation. COLD was a nationally representative, population-based cross-sectional study of 3,042 Canadians 40 years of age or older(25). Using these data, we developed sex-specific logistic regression equations for the probability of having COPD as a function of sex, age, and smoking pack-years ( Table 1 and Appendix 3 ).…”
Section: Methodsmentioning
confidence: 99%